We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive pseudonymised information about your use of our website. cookie policy and privacy policy.
 
+0  
 
0
176
1
avatar+1206 

Let r, s, and t be the roots of \(2x^3 - 7x^2 - 6 = 0\). Find rst.

 Jun 5, 2019

Best Answer 

 #1
avatar+844 
+1

rst = -d/a

rst = -(-6)/2

rst = 3

 Jun 5, 2019
 #1
avatar+844 
+1
Best Answer

rst = -d/a

rst = -(-6)/2

rst = 3

YEEEEEET Jun 5, 2019

13 Online Users

avatar